Developing metrics for emerging technologies: identification and assessment - Zamani, Mehdi; Yalcin, Haydar; Naeini, Ali Bonyadi; Zeba, Gordana; Daim, Tugrul U (Technological forecasting & social change, 2022)
•current research topics in the field of emerging technologies•direction of future research in the field of emerging technologies•a new approach to assess emerging technologies We analyze the field of emerging technologies using bibliographic techniques. The Web of Science (WoS) citation database was used as an article retrieval tool in this study. To analyze the studies, first the files received from the mentioned database were integrated by Bibexcel software. Then, the process of "current technologies” was studied from 1969 to 2020 by the Bibliometrix package from Bibliometrics and SciMat software, as well as thematic evolution maps and strategic diagrams. To identify the main actors and resources in these areas, the results obtained from the analysis indicated highly cited articles, journals, and influential authors in this field. In addition, the results of evaluating strategic diagrams and thematic evolution maps revealed the topics of emerging technologies. In general, the topics and technologies such as "Internet of Things (IoT)", "Intelligent Transportation Systems (ITS)", "Ultrasound", are among the emerging areas and technologies being considered during the last decade as the most central topics. Structural hole analysis has been applied to determine the sub-technologies of these technologies that have begun to mature. Furthermore, the trend of research focus on these topics has been increasing. For this reason, to determine the sub-subject areas that are open to improvement, they are handled with low aggregate constraints values.